QUASI-EXPERIMENTAL VAK LEARNING MODEL IN GRAPHIC DESIGN SUBJECTS IN CLASS X TKJ SMK NEGERI 1 TEGALBULEUD - Hendra, Hendra; Yudianto, Arif; Rahmat, Dadan (Universitas Lampung, 2021)
This study aims to determine whether there are differences in learning outcomes between students who were treated with the VAK (Visual, Auditory, Kinesthetic) learning model and students who were treated with the demonstration learning model in graphic design subjects. This type of research uses a quasi-experimental. This research was conducted at SMK Negeri 1 Tegalbuleud. The sample in this study were all 32 students of class X TKJ and were divided into two groups, namely the experimental group (16 students) and the control group (16 students). The sampling technique used was purposive sampling. The research instrument uses a test instrument with the type of knowledge test and is presented in the form of multiple choice which has been tested for validity and reliability. Data collection techniques using pretest and posttest. Data analysis technique using t test. The results showed that there were differences in learning outcomes between the experimental group that applied the VAK learning model (Visual, Auditory, Kinesthetic) and the control group that applied the demonstration learning model. The average value of the pretest in the experimental class is 46.44 and the average posttest in the experimental class is 89.13. While the average value of the pretest in the control class is 46.44, and the average value of the posttest in the control class is 82.47. The results of the Independent-Samples T Test show that the value of Sig. 2-tailed = 0.023 < 0.05. This shows that Ho is rejected and Ha is accepted. Keywords: Basic Graphic Design, Quasi-Experimental, VAK models, Visual Auditory Kinesthetic.DOI: http://dx.doi.org/10.23960/jpvti.v3.i2.202101